The Theological Importance Of Creation In The Old Testament - Gołębiewski, Marian (Studia Theologica Varsaviensia, 2020)
+. It is true that the concept of creation takes on theological focus in Israel quite late. e chosen nation was primarily interested in history and its relation to God, and then asked a question about the beginning of the world. Over time, as a result of historical events, it gradually developed a lesson on creation. Babylonian slavery played a decisive role in the theological reflection on creation. &. e Old Testament texts testify that the statement “Yahweh has made heaven and earth” corresponds to a threefold theological intention. It has at the same time a doxological, soteriological and polemic character. e Old Testament taken as a whole evokes a cosmogonic fact to praise the glory of the God of Israel and emphasise His transcendence, to question the worship of nature, freeing man from the caring cosmic and agrarian forces, and to guarantee salvation for Israel and the world, relying on the power of God, able to make all things new out of love for his chosen. 3. e Old Testament shows us that the theological reflection on the creation of the world and mankind has been expressed in various forms in the history of Israel, there is no single formula of Israel’s faith in creation, but it is always about the same faith expressed in a formulation conditioned by the current cultural context, always with the triple theological intentions mentioned above. is can be seen in the Old Testament writings, starting with the Jehovah and the priestly writer, through Deutero-Isaiah and the author of the Book of Job, whose faith was later expressed in the first article of the creed: “I believe in God the Almighty Father, the Creator of heaven and earth.”